RESEARCH TRENDS IN THE CONSTRUCTION INDUSTRY RUSSIAN FEDERATION - Khairullina, Albina; Nabieva, Larisa; Sabirova, Aigul (Gênero & Direito, 2019)
This article analyzes the current state of the construction industry of the Russian Federation at the federal and local (for example, the Republic of Tatarstan) levels. The features and trends of the construction industry of the Russian Federation (RF) are considered, taking into account the changes in the legislation affecting this industry. The authors analyzed the statistics of housing commissioning, the dynamics of lending and debt of construction organizations, in addition, the analysis of statistics of bankruptcies of companies. The key players in the construction market of the Republic of Tatarstan were studied, and their reliability rating was presented. Based on the results of the analyzed material, certain conclusions were formulated. Based on the findings, it was determined that in the Russian Federation the construction industry is experiencing some difficulties that require special attention from the state. However, at present the government is already taking certain steps towards improving the current situation. As it was revealed, in the Republic of Tatarstan, the construction industry has had a positive development dynamics over several years. In recent years, there has been an increase in housing commissioning. In addition, the government annually invests in the construction industry. Despite this, in Tatarstan there is a high percentage of bankruptcies of construction companies, the reasons for which are identified in this article.